La participación de las organizaciones sociales de la parroquia San Simón en la gestión del agua - Salazar Armijo, Sandra Maribel (2015)
Through this research work, we present the different perspectives of development through participation of stakeholders in water management in the parish of St. Simon, Guaranda Canton, and Bolivar Province. The lack or no participation of stakeholders in the proper management and water conservation through the protection, maintenance sheds water birthing, and being a vital liquid for human consumption, in some cases for irrigation makes this research project is imminent necessity and purpose to counteract this global phenomenon of decreased water in our Andean highlands Parish San Simon. Moreover, knowing that the parish is an area of overgrown flora and fauna, has made us to worry about conservation, environmental protection, for the welfare of the population San Simonen, the same pretending declare an eminently Ecological Parish and Tourism. At the level of diagnosis, it is noted that the main problems faced in this field are accelerated loss of biodiversity, poor environmental awareness of environmental problems, reduced flows and pollution of water systems and accelerated loss of forests. The difficulty is how to make this process of struggle in a process of political awareness, a process in which people understand that the struggle for demands going beyond asking, goes further to see who support us and that we should have participation to reach the same rights determine where state resources are invested, and how each one will play what rightfully belongs. In this context the present research seeks to answer the key question: how changes in the participation of local organizations, management and management of water sources in the parish of St. Simon, Canton Guaranda, Bolivar Province it has changed the type of use and the degree distribution of water resources is productive or drinking purposes. To answer this question, this paper is part of an academic and social reflection on paradigms, methodologies and successful experiences of sustainable local development, to resume the local and global dimensions. Thus, it is linked to academic work with the regional environment through actions that promote the participation of